Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan Pada PT Makassar Tene - Andi Fajriansyah (Jurnal Online Manajemen ELPEI, 2021)
This study entitled "The Influence of Job Training on Employee Performance at PT. Makasar Tene". This study aims to determine how much influence Job Training has on Employee Performance. This research was conducted at PT. Makassar Tene at the end of August to the end of October. Sampling in this study was 72 respondents, the data collection technique was through questionnaires distributed to respondents, while the research variables were job training (X), employee performance (Y). This study uses descriptive analysis with a quantitative approach, and to test the level of reliability using Cronbach Alpha and then the data is processed by Simple Linear Regression Analysis. Hypothesis testing uses the t test with a significance level of 5%. This study used the SPSS Version 25 tool. From the results of simple linear regression analysis, it shows that employee performance is influenced by the Job Training variable. Determination results (R2) use the adjusted r square value, because it uses a regression with one dependent variable. That is equal to 0.671, which means that the Job Training variable is able to explain Employee Performance by 67.1% while the remaining 32.9% is influenced by other variable factors not examined. From the results of the t test calculations, it can be seen that the Job Training variable has a partial effect on Employee Performance.